PENGARUH INFLASI, NILAI TUKAR, HARGA MINYAK KELAPA SAWIT TERHADAP HARGA SAHAM SUB SEKTOR PLASTIK DAN KEMASAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Rosdiana (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2023)
This study aims to analyze how inflation, exchange rates, and palm oil prices affect stock prices in the plastics and packaging sub-sector plantations listed on the Indonesia Stock Exchange in 2015-2021. The sampling technique used was purposive sampling with certain criteria. A sample of 9 plastic and packaging sub-sector companies registered on the IDX during the 2015-2021 observation period. The analysis technique used is multiple regression equations to obtain a linear estimation model containing. The hypothesis was tested using t-statistics to test the significance of the partial regression coefficients. From the test results, there are two independent variables that effect stock prices in companies in the plastics and packaging subsector CPO prices and exchange rates, while the other independent inflation has no significant effect on plastic and packaging stock prices.